Biofouling and short-term dynamics on fish cage netting in relation to fish rearing and environmental factors / John Madin - Madin, John (2010)
Four studies were conducted in a floating net-cages farm at Matang Mangrove Forest Reserve (MMFR), Perak, Malaysia, to elucidate the biofouling assemblages on cage nettings and factors that influence their development. In the first study (Chapter 3),biofouling on 1.6 cm mesh net panels (size 0.2 m x 2 m) suspended inside (homemade pellet ‘P’, trash fish ‘T’) and outside (O) experimental net-cages in a fish farm were monitored every week until net openings were completely occluded by macrofouling organisms. Eight species (7 phyla) of sessile organisms and 27 species (3 phyla) of nonsessile associates were recorded.Colonization by macrofouling organisms usually began with Plumularia sp. and Gammaropsis sp. while other species only appeared after 1 or 2 weeks of net panels immersion. Inside net-cages where water flow was slow(mean < 6 cm s-1), macroalgae (Polysiphonia sp.), anthozoans (unidentified anemones),barnacles (Balanus amphitrite), amphipods (Gammaropsis sp. & Photis sp.) and tanaids(Leptognathia sp.) were dominant on the net panels during the dry season. However, in the wet season, hydroid (Plumularia sp.), mussel (Xenostrobus mangle), nematode and copepods (Euterpina acutifrons) abundance was significant. With stronger water flow (mean ≈20 cm s-1) as occurring outside net-cages, macrofouling assemblages for both seasons comprised mainly Plumularia sp. and Gammaropsis sp.. The macrofouling assemblage showed a clear succession of species that occupied different depths of the net panels.It was hypothesized from the first study (Chapter 3) that the use of high quality fish pellet feed should reduce feed wastage and thus biofouling assemblages. However, as revealed in the second study (Chapter 4), the biomass of sessile macrofoulers and their non-sessile associates on net panels inside the net-cages given the high quality feed (commercial pellet ‘M’) was not significantly (P > 0.05) different to that given low quality fish feed (homemade pellet ‘P’ & trash fish ‘T’). These results do not support the proposed hypothesis that a high quality fish feed could help to reduce biofouling assemblages on nets. A reduced flow rate to less than 10 cm s-1 inside the net-cage will significantly encourage the rapid development of sessile biofouling biomass (g m-2 wk-1), with (175 to 231% higher in treatments M, P & T) or without (56 to 145% higher in treatments N) fish rearing and feed input compared to swifter water flow i.e. >25 cm s-1 outside net-cages (C). However, non-sessile organisms were more attracted to the organic inputs from fish rearing inside the net-cages (i.e. whether M, P & T); their biomass (g m-2 wk-1) were 459 to 802% higher compared to treatments without fish rearing and feed input (N) or outside net-cages (C). The physical presence of the netcage units and net biofouling play a significant role in flow attenuation. However, there was no significant (P > 0.05) effect on biofouling due to net-cage position in the fish farm suggesting that the water flow regimewithin the cage farm was rather consistent.It was also hypothesized from the first study (Chapter 3) that the higher salinity during the dry season favoured marine and euryhaline forms and thus increases biofouling rates. However, as revealed in the third study (Chapter 5), survival and development of macrofouling assemblages were not solely influenced by salinity but a combination of salinity as well as other abiotic and biotic factors. The fourth study (Chapter 6) revealed that concentration of dissolved nutrients and chlorophyll-a was relatively higher inside the net-cages (pellet ‘P’& trash fish ‘T’) than outside it (O), suggesting that fish rearing and fish feed input contribute to nutrient and phytoplankton enrichment of culture waters. This finding is consistent with findings from the first study (Chapter 3) where population and total wet biomass of macrofoulers were found to be significantly (P < 0.05) higher inside the net-cages (P, T) than outside it (O).From the study, it is recommended that, in order to reduce biofouling rates and improve water quality, floating fish cage farms in tropical estuaries should be carefully sited (to receive maximum water flow) and re-designed (to improve water flow rates).Furthermore, the rearing of fish fingerling which requires fine-mesh (1.6 cm) should preferably begin during the wetter months and located around the farm’s periphery so as to reduce biofouling and net clogging.